Observing Nearby Nuclei on Paramagnetic Trityls and MOFs via DNP and Electron Decoupling. Issue 68 (11th October 2022) - Tan, Kong Ooi; Yang, Luming; Mardini, Michael; Boon Cheong, Choon; Driesschaert, Benoit; Dincă, Mircea; Griffin, Robert G.
Abstract: Dynamic nuclear polarization (DNP) is an NMR sensitivity enhancement technique that mediates polarization transfer from unpaired electrons to NMR‐active nuclei. Despite its success in elucidating important structural information on biological and inorganic materials, the detailed polarization‐transfer pathway from the electrons to the nearby and then the bulk solvent nuclei, and finally to the molecules of interest‐remains unclear. In particular, the nuclei in the paramagnetic polarizing agent play significant roles in relaying the enhanced NMR polarizations to more remote nuclei. Despite their importance, the direct NMR observation of these nuclei is challenging because of poor sensitivity. Here, we show that a combined DNP and electron decoupling approach can facilitate direct NMR detection of these nuclei. We achieved an ∼80 % improvement in NMR intensity via electron decoupling at 0.35 T and 80 K on trityl radicals. Moreover, we recorded a DNP enhancement factor of ϵ ε ∼90 and ∼11 % higher NMR intensity using electron decoupling on paramagnetic metal‐organic framework, magnesium hexaoxytriphenylene (MgHOTP MOF). Abstract : Electron decoupling (eDec) attenuates the electron‐nuclei hyperfine interaction (depicted as the magenta sphere) and, thus, improves the NMR sensitivity by ∼80 %. Furthermore, the combined DNP and eDec technique reveals that the intramolecular nuclei in trityl and paramagnetic MgHOTP MOF are outside the spin diffusion barrier.